The bilingual reading practices and performance of two Hispanic first graders - López-Velásquez, Angela M.; García, Georgia Earnest (Bilingual Research Journal, 2017)
This qualitative study used a sociocultural lens to examine how two bilingual Hispanic first-grade girls demonstrated bilingual reading practices (i.e., heteroglossia and translanguaging) as they discussed and read texts in Spanish and English. One girl predominantly received school reading instruction in Spanish, while the other received school reading instruction in English. They both participated in Spanish reading at home. The school reading instruction employed Spanish or English versions of Success for All, and emphasized word recognition strategies appropriate for the language of instruction along with meaning-making strategies. In April, the two girls scored mid- to end-of first grade on a curriculum-based reading assessment in the language of instruction. Neither of them received biliteracy instruction. Their reading levels in the instructional language and exposure to the other language appeared to be sufficient for them to develop and demonstrate heteroglossic practices. Bilingual dynamic reading assessments and home reading sessions with a bilingual researcher revealed that both girls utilized bilingual reading practices to discuss and comprehend texts in their non-instructional or alternate language. One of the girls also used bilingual reading practices to discuss texts in the instructional language. To read in the alternate language, they both employed word-recognition and meaning-making strategies, which had been emphasized in their school reading instruction. However, one girl’s attempt to use a decoding strategy she had learned in English (i.e., onset-rime) to decode unfamiliar Spanish words did not work effectively. Implications are delineated for the bilingual reading instruction and assessment of young bilingual children.
Keywords: dept.sed

Leveraging information technology literacy to enhance college and career readiness for secondary students with disabilities - Lombardi, Allison; Izzo, Margo V.; Gelbar, Nicholas; Murray, Alexa; Buck, Andrew; Johnson, Victor; Hsiao, Jay; Wei, Yan; Kowitt, Jennifer (Journal of Vocational Rehabilitation, 2017)
BACKGROUND: In the 21st century, information technology (IT) literacy is crucial for all students, and may better prepare students with disabilities for transition to postsecondary employment or education. OBJECTIVE: In this study, the potential of IT literacy embedded into an online transition curriculum is explored in the context of secondary special education. The curriculum aligns with Common Core State Standards in English Language Arts that are relevant to reading comprehension, writing, as well as searching for and analyzing sources of information online. METHODS: A quasi-experimental pretest-posttest design was utilized in six high schools. RESULTS: Findings show that intervention group students improved in IT literacy; whereas, comparison group students did not make similar gains. CONCLUSION: Implications for embedding transition services into specific courses and curricula for secondary students with Individualized Education Programs (IEPs) are discussed. © 2017-IOS Press and the authors. All rights reserved.
Keywords: Article; Transition; adolescent; attention deficit disorder; autism; career; career readiness; college; comprehension; controlled study; curriculum; dept.rdg; dept.sed; disability; education program; emotional disorder; employment; female; high school student; human; information technology; intellectual impairment; language disability; learning disorder; literacy; major clinical study; male; quasi experimental study; special education; technology; vocational education; writing

Transition issues and challenges for youth with autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L. J.; Hart, Logan (Pediatric Annals, 2017)
Keywords: dept.aa; dept.sed

Participation of students with intellectual and developmental disabilities in extracurricular activities: does inclusion end at 3:00? - Agran, Martin; Achola, Edwin; Nixon, Cynthia Allen; Wojcik, Andrew; Cain, Irma; Thoma, Colleen; Austin, Kira M.; Tamura, Ronald B. (Education and Training in Autism and Developmental Disabilities, 2017)
Although participation in extracurricular activities for students with intellectual and developmental disabilities has been advocated, a limited number of students appear to be involved in such activities. Further, there is little empirical research on how extracurricular activities are valued, supported, and encouraged. This study surveyed a sample of special educators across five states to learn about their opinions regarding extracurricular activities. As reported in other research, the findings confirm that few students participated in these activities; few parents requested these services for their children; and few teachers believed that planning them is their responsibility, despite the fact that they thought these activities were of value and provided several benefits. The implications of these findings are discussed.
Keywords: dept.sed

Teaching students to write: Arguing against the overuse of argument - Randall, Régine; Mercurio, Mia Lynn (Kappa Delta Pi Record, 2017)
This personal editorial written by two education professors considers the Common Core State Standards and argues against the overuse of argument in the teaching of writing. © Kappa Delta Pi.
Keywords: Common core; Writing; dept.cur; dept.sed

Exploring English and Spanish rhyme awareness and beginning sound segmentation skills in prekindergarten Spanish-speaking English Learners - Raynolds, Laura B.; López-Velásquez, Angela; Olivo Valentín, Laura E. (Reading and Writing, 2017)
Twenty-five 4- and 5-year-old Spanish-speaking English Learners (ELs) were tested in order to compare their English and Spanish performance in two phonological awareness skills: Rhyme awareness (RA) and beginning sound segmentation (BSS). The children had received formal instruction of phonological awareness, with an emphasis on RA and BSS for 1 year and in English only, using the Opening the World of Learning curriculum (Schickedanz & Dickinson, 2005). The results showed that the children scored higher on the English BSS than on the English RA tests (p ¡ .001), even though RA is generally considered to be an earlier developing skill than BSS among English-monolingual children. No significant difference was found between the English BSS and Spanish BSS tests despite the fact that the children had received English-only instruction in these phonological awareness skills for 1 year. The results are discussed in terms of the possible impact of the similarities and differences between the Spanish and English linguistic structures on the learning and cross-linguistic transfer of phonological awareness skills in young Spanish-speaking ELs.
Keywords: Beginning sound segmentation; English-only instruction; Phonological awareness; Prekindergarten; Rhyme awareness; Spanish-speaking English Learners; dept.cur; dept.sed; peer-reviewed

A revised embedded planning tool for intensive reading instruction - Wei, Yan; Lombardi, Allison; Simonsen, Brandi; Coyne, Michael; Faggella-Luby, Michael; Freeman, Jennifer; Kearns, Devin (Learning Disabilities: A Multidisciplinary Journal, 2017)
Keywords: dept.rdg; dept.sed